1990
DOI: 10.1161/01.atv.10.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Pre-beta high density lipoprotein. Unique disposition of apolipoprotein A-I increases susceptibility to proteolysis.

Abstract: Apolipoprotein A-l-contalnlng llpoprotelns (high density llpoproteins, HDL) can be separated Into two subtractions, which have pre-beta and alpha electrophoretic mobilities, respectively. These fractions differ In both composition and structure. Some preparations of pre-beta-mlgratlng HDL, but not alpha-migrating HDL, were found to contain two polypeptldes with M r of approximately 26 and 14 kDa, which are scission products of apolipoprotein (apo) A-l. They are recognized by monospeclflc antibodies to apo A-l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 17 publications
4
51
0
5
Order By: Relevance
“…2A). Previous studies established that the lipid composition of pre-␤ 1 -LpA-I species as well as the conformation of apoA-I within these particles differ from those of spherical HDL (25,30). Furthermore, pre-␤ 1 -LpA-I is proposed to be an initial acceptor of cell-derived cholesterol (30).…”
Section: Discussionmentioning
confidence: 99%
“…2A). Previous studies established that the lipid composition of pre-␤ 1 -LpA-I species as well as the conformation of apoA-I within these particles differ from those of spherical HDL (25,30). Furthermore, pre-␤ 1 -LpA-I is proposed to be an initial acceptor of cell-derived cholesterol (30).…”
Section: Discussionmentioning
confidence: 99%
“…13 Specifically, the highaffinity component of LpA1, HDL 3 , and plasma that promotes cholesterol efflux from macrophage foam cells is sensitive to proteolysis by the neutral protease chymase contained in exocytosed mast cell granules, ie, the granule remnants. 32 Because pre␤ 1 LpA1 promotes rapid and specific cholesterol efflux from cell cultures 25 and is sensitive to proteolysis, 45 it seemed very likely that the proteolysissensitive component of the cholesterol efflux capacity of HDL and plasma was, in fact, caused by the presence of this particle. To test this hypothesis, we used 2 experimental approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, these might include catabolism by cells, although tissue culture studies have indicated that this is unlikely to be quantitatively significant. 39 Because pre-␤ HDLs are more susceptible to proteolysis than are other HDLs, 40 they might be degraded by enzymes released into tissue fluid, 41,42 although no apoA-I fragments were detected in our HP-SEC fractions of lymph. A third possibility is that some small pre-␤ HDLs are converted in tissue fluid into larger discoidal species that are incompletely resolved by our laboratory procedures, as a consequence of uptake of cell-derived PL and UC.…”
Section: Nanjee Et Almentioning
confidence: 91%